Pengaruh Metode Directed Reading Thinking Activity (DRTA) Terhadap Kemampuan Membaca Intensif Pada Materi Teks Pokok Bacaan di Kelas III Sekolah Dasar - Sri Nurafifah; Cucu Rojikin; Irfan Fajrul Falah (Universitas Muhammadiyah Kuningan, 2024)
The research purpose to determine the implementation of the Directed Reading Thinking Activity (DRTA) method and to determine the effect of the Directed Reading Thinking Activity (DRTA) method on intensive reading skills on the main material of reading texts in class III of elementary school. The research method used in this research is a quantitative method with the research subjects being 29 grade III elementary school students. Data was collected through library studies, field studies, learning processes, questionnaires and tests. Then the data is processed, analyzed using statistical tests to obtain results and conclusions. The results of this research show that the Directed Reading Thinking Activity (DRTA) learning method can improve reading skills in third grade elementary school. The increase in students' reading skills can be seen in the quality of the learning process which is shown by students' activity and enthusiasm during the learning process. The product improvement can be seen from the percentage of student responses to the application of the Directed Reading Thinking Activity (DRTA) method of 78.15% and if interpreted, the response was very positive and the average score of students increased before being given the application of the Directed Reading Thinking Activity (DRTA) method. 51.90%, after being given the application of the Directed Reading Thinking Activity (DRTA) method 75.66, an increase of 43.85%.